2016
DOI: 10.4238/gmr.15017809
|View full text |Cite
|
Sign up to set email alerts
|

APOA5 polymorphisms associated with lipid metabolism in Brazilian children and adolescents

Abstract: ABSTRACT. Single nucleotide polymorphisms in the APOA5 gene have been studied for their association with metabolic syndrome. Thus, elucidating the effect of the mechanism involved in APOA5 gene polymorphisms on lipid metabolism is of great importance. In this study we aimed to determine the allelic and genotypic frequencies of -1131T>C, Ser19Trp, and intergenic APOA4/A5 and to evaluate the association between these variants with plasma lipid levels in children and adolescents from Brazil. This study included 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…After filtering by availability and reading, consisting of reading the title, abstract, and keywords of each study, 15 articles were selected (Table 1). [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] the remainder were excluded from the analysis, because they were not aligned with the subject of the review or with the inclusion parameters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After filtering by availability and reading, consisting of reading the title, abstract, and keywords of each study, 15 articles were selected (Table 1). [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] the remainder were excluded from the analysis, because they were not aligned with the subject of the review or with the inclusion parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The foci of identification of the studies selected were investigations of associations between a given genetic polymorphism of a gene involved in the process of a metabolic pathway and risk factors for MS, such as obesity, dyslipidemia, insulin resistance, and hypertension (Table 2). [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The relationship between differences in the polymorphic frequency of genes involved in obesity and MS was analyzed in five studies with samples of adults and adolescents with different population profiles. One of them found that nutritional control and exercise may be more effective at preventing risks associated with MS in individuals with the A allele for polymorphism 48867A> C (Asp358Ala) IL6R (rs2228145).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several genes are related to lipid metabolism. [8] Apolipoprotein A5 (APOA5) is considered a risk factor for CVD,[9] with an increase of triglycerides and a lowering of HDL-c in boys, but not girls. [10] Naturally occurring variants of the APOA5 gene have been associated with increased triglyceride levels and have been found to confer risk for CVDs.…”
Section: Introductionmentioning
confidence: 99%